PEMANFAATAN LIMBAH PENAMBANGAN NIKEL SOROAKO (OVERBURDEN) SEBAGAI PREKURSOR KATALIS PROSES PENCAIRAN BATUBARA - Adiarso Adiarso; Muhammad Hanif (Jurnal Energi dan Lingkungan (Enerlink), 2005)
Previous studies have shown that limonit ore has several outstanding characteristics compared to pyrite when used as catalyst in coal liquefaction process. One of the reasons is, that limonit ore containsÂ Î±-FeOOH compound, which is responsible for the high activity. This study is aimed to investigate the catalyst performance of Soroako limonit ore using a 1-liter autoclave in comparison with other catalyst for liquefaction. The investigation suggested that pyrrhotite, the active phase that transformed from FeOOH occurred at low temperature, meaning that the availability of this phase before the thermal decomposition of coal takes place is responsible for its high activity. Moreover, from its physical property point of view, Soroako limonit has superior nature in that, it is rather soft that pyrite, making the pulverization into sub-micron sizes possible. These all properties suggest that Soroako limonit becomes the important candidate catalyst for industrialization of direct coal liquefaction.Kata kunci: Liquefaction, limonit, catalyst, hydrogenation, catalytic, coal, Soroako